Accuracy of dual‐bolus CT in the diagnosis of active arterial bleeding in adult pelvic trauma. Issue 3 (3rd April 2020) - Harisis, George N; Lee, Jonathan TL; Clements, Warren; Joseph, Tim; Goh, Gerard S
Abstract: Introduction: A single‐phase dual‐bolus CT (DB‐CT) simultaneously opacifies both arterial and venous systems and can be utilised in the trauma setting to aid in the diagnosis of active bleeding while also allowing for optimal assessment of the abdominal and pelvic viscera. Active bleeding can be venous or arterial, the latter being amenable to angiography and potentially embolisation. We aimed to establish the accuracy of single‐phase DB‐CT vs commonly performed portal venous CT (PV‐CT) in the diagnosis of active bleeding when compared to formal digital subtraction angiography as the gold standard. Methods: All patients diagnosed with active bleeding on PV‐CT or DB‐CT at a level 1 tertiary centre over a 6‐year period and who subsequently proceeded to digital subtraction angiography (DSA) were included for analysis. The initial CT images were retrospectively reviewed by two consultant interventional radiologists who were blinded to the subsequent outcome of the DSA and to each other's results. The sensitivity, specificity and inter‐observer agreement between the two readers was then able to be assessed. Results: A total of 60 patients were included in the analysis. Sensitivity for the diagnosis for any active bleeding was high for both DB‐CT and PV‐CT (range 88.9%–100%) while diagnosis of specifically arterial bleeding was comparatively lower (51.9%–79%). Inter‐observer agreement for the identification of arterial bleeding was better for DB‐CT (fair) compared to PV‐CT (poor). Conclusion: Both PV‐CT and DB‐CT demonstrate high sensitivity in the diagnosis of any active bleeding though identification of specifically arterial bleeding is lower for both scanning methods. Nevertheless, inter‐observer reliability for the identification of arterial bleeding is higher for DB‐CT. Multi‐phase arterial and venous CT may yield better results and could be a focus for future studies.